Agile Modeling of Production Price with Adaptive Precision - Šketa, Anja; Čevka, Andraž; Jagodic, Dominik; Šter, Darja; Rifl, Matija; Bokal, Drago (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
Digitalization and process optimization in companies are increasingly popular. However, only a small part of the overall promotion is dedicated to raising awareness of the actual models and accurately valued benefits of process optimization for businesses. Specific insights into the modelling process seem to be obscured by protecting competitive advantages. Methodology of assessment of their value or even just accurate savings are hard to come by. We present a successful case study of process optimization conducted at Exoterm-IT d.o.o. The foundation for process optimization is the calculation of the company's products production price. We present an iterative modeling process together with indicators of value added by growing model complexity in current and subsequent iteration. This process allows the company to compromise in accuracy vs. complexity of the model they apply for their decision making, as well as identifies relevance of the segments of production cost for possible optimisation.